Liberalisasi Keuangan dan Pembangunan Ekonomi: Belajar dari Krisis Ekonomi Indonesia - Allo, Albertus Girik (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 2, Agustus 2016 (pp. 89 - 176), 2017)
The purpose of this study to see how the relationship between the liberalization of the financial sector to the economy in Indonesia and how the shocks caused by the crisis affect the financial sector. The approach using the time series data set with time periode 1980-2013 were sourced from World Bank and Vector Error Correction Model (VECM) as a method of estimation. The results showed that the shocks that occurred in GDP will cause changes in the financial sector, especially percentagedomestic credit to private sector in GDP. In addition, variable crisis and percentage domestic credit to private sector in GDP shows bi-directional causality.
Keywords: pembangunan ekonomi; liberalisasi keuangan; Produk Domestik Bruto/PDB; krisis ekonomi; Vektor Error Correction Model (VECM)